THE CATALYTIC DECOMPOSITION OF PETROLEUM INTO NATURAL GAS - Mango F.D.; Hightower J. (My University, 1997)
Petroleum is believed to be unstable in the earth, decomposing to lighter hydrocarbons at temperatures > 150°C. Oil and gas deposits support this view: gas/oil ratios and methane concentrations tend to increase with depth above 150°C. Although oil cracking is suggested and receives wide support, laboratory pyrolysis does not give products resembling natural gas. Moreover, it is doubtful that the light hydrocarbons in wet gas (C2-C4) could decompose over geologic time to dry gas (>95% methane) without catalytic assistance. We now report the catalytic decomposition of crude oil to a gas indistinguishable from natural gas. Like natural gas in deep basins, it becomes progressively enriched in methane: initially 80% (wet gas) to a final composition of 100% methane (dry gas). To our knowledge, the reaction is unprecedented and unexpectedly robust (conversion of oil to gas is 100% in days, 175°C) with significant implications regarding the stability of petroleum in sedimentary basins. The existence or nonexistence of oil in the deep subsurface may not depend on the thermal stability of hydrocarbons as currently thought. The critical factor could be the presence of transition metal catalysts which destabilize hydrocarbons and promote their decomposition to natural gas.